2008
DOI: 10.1002/dvdy.21453
|View full text |Cite
|
Sign up to set email alerts
|

A hedgehog homolog is involved in muscle formation and organization of Sepia officinalis (mollusca) mantle

Abstract: Our study focuses on the possible involvement of the Hedgehog (Hh) pathway in the differentiation of striated muscle fibres in cuttlefish (Sepia officinalis) mantle. We show here that both an hh-homolog signalling molecule and its receptor Patched (Ptc) are expressed in a specific population of myoblasts which differentiates into the radial fast fibres. To evaluate the functional significance of hh expression in developing cuttlefish, we inhibited the Hedgehog signalling pathway by means of cyclopamine treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…The limited knowledge about these important pathways is restricted to some gene expression studies in a few gastropod and cephalopod representatives [105, 106]. Comparisons with respect to the core components present in these two pathways between the transcriptomes described here and two molluscan reference genomes (the limpet Lottia gigantea and the oyster Crassostrea gigas ) revealed a highly shared molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…The limited knowledge about these important pathways is restricted to some gene expression studies in a few gastropod and cephalopod representatives [105, 106]. Comparisons with respect to the core components present in these two pathways between the transcriptomes described here and two molluscan reference genomes (the limpet Lottia gigantea and the oyster Crassostrea gigas ) revealed a highly shared molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was highly increased in heavy infections by Bonamia spp. The transmembrane protein, patched, is a receptor for the morphogene sonic hedgehog, leading to multiple hedgehog transduction signals (Grimaldi et al, 2008). Its transcript appeared overexpressed by Q-PCR in infections by Bonamia spp.…”
Section: Othersmentioning
confidence: 99%
“…While the general make-up of the mantle musculature is very different from that of the decabrachian tentacle, similar muscle precursor cells seem to contribute to the formation of this muscle tissue in the cuttlefish S. officinalis (Grimaldi et al, 2008). In particular, the early cuttlefish mantle consists of a compact mass of elongated and spherical muscle precursor cells, surrounded by a multilayered integument (Figure 2C, Table 1).…”
Section: Muscle Morphogenesis In Cephalopodsmentioning
confidence: 99%
“…During mantle muscle maturation radial fibers divide circular muscle fibers into parallel rows while circular musculature differentiates into the superficial slow muscle fibers (outer and inner region of the mantle) and the deeper fast circular fibers (central and radial fibers). Grimaldi et al (2008) have further shown that during this process the proliferation and survival of myogenic precursor cells seems to depend on the signaling molecule Hedgehog (Hh) and its receptor Patched (Ptc). In vertebrates the proliferation of myoblast cells is mostly regulated by fibroblast growth factors (FGFs), but the vertebrate Hh ortholog Sonic hedgehog (Shh) is similarly required for the determination of muscle precursor cells in both trunk and limb musculature (Borycki et al, 1999; Bren-Mattison and Olwin, 2002; Table 1).…”
Section: Muscle Morphogenesis In Cephalopodsmentioning
confidence: 99%